2021
DOI: 10.1175/jcli-d-20-0871.1
|View full text |Cite
|
Sign up to set email alerts
|

Testing Methods of Pattern Extraction for Climate Data Using Synthetic Modes

Abstract: In this paper we develop a method to quantify the accuracy of different pattern extraction techniques for the additive space–time modes often assumed to be present in climate data. It has previously been shown that the standard technique of principal component analysis (PCA; also known as empirical orthogonal functions) may extract patterns that are not physically meaningful. Here we analyze two modern pattern extraction methods, namely dynamical mode decomposition (DMD) and slow feature analysis (SFA), in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The reason for this statement was the common assumption that the first few modes returned by PCA are physically interpretable and match the underlying signal in the data. However, Fulton and Hegerl (2021) tested this signal-extraction 365 method and demonstrated that it has serious deficiencies when extracting multiple additive synthetic modes (false dipoles instead of monopoles, which may lead to serious misinterpretation of extracted modes). They also found that PCA tends to mix independent spatial regions into single modes.…”
Section: Initialization Of Classes 360mentioning
confidence: 99%
“…The reason for this statement was the common assumption that the first few modes returned by PCA are physically interpretable and match the underlying signal in the data. However, Fulton and Hegerl (2021) tested this signal-extraction 365 method and demonstrated that it has serious deficiencies when extracting multiple additive synthetic modes (false dipoles instead of monopoles, which may lead to serious misinterpretation of extracted modes). They also found that PCA tends to mix independent spatial regions into single modes.…”
Section: Initialization Of Classes 360mentioning
confidence: 99%
“…Previous oceanic and atmospheric studies have made significant efforts in geographic data analysis to extract patterns from simulated and observed gridded geographic data sets (Hannachi, 2007; Meehl et al, 2005). These patterns can further aid the investigation of the physical mechanisms behind these signals and thus to improve understanding of the physical processes that generate oceanic and climate variability and teleconnections (Fulton & Hegerl, 2021). Empirical orthogonal functions (EOFs) are the one of the most widely used methods to find patterns of variability from high‐dimensional geographic data.…”
Section: Introductionmentioning
confidence: 99%
“…understanding of the physical processes that generate oceanic and climate variability and teleconnections (Fulton & Hegerl, 2021). Empirical orthogonal functions (EOFs) are the one of the most widely used methods to find patterns of variability from high-dimensional geographic data.…”
mentioning
confidence: 99%
“…Although the development of verification datasets for advanced data analytic techniques in the climate community is nascent, there are a few examples. Fulton and Hegerl (2021) generated synthetic climate modes to test the accuracy of distinct pattern extraction techniques and show that the most commonly used principal component analysis technique does not perform well. Mamalakis et al (2022) worked to develop an "attribution benchmark dataset" for which the ground truth is known to enable evaluation of different explainable artificial intelligence (AI) methods.…”
Section: Introductionmentioning
confidence: 99%